Managerial virtues: Perspectives of future knowledge workers - Yen, Wan Chong; Ismail, Mohd Nazari; Thi, Lip Sam (2017)
Virtues are essential moral attributes of successful managers in the knowledge economy. Business ethics and moral virtues facilitates the development of intellectual capital which are the most important resources of organizations today. Many have even argued that the lack of moral virtues of business executives is one of the root causes of recent financial crises.Virtues are character traits or qualities that are deemed to be morally good. However, there is a general lack of agreement on what virtues are as well as the types of virtues a good manager should possess. Cross-national studies have found that managers from different countries accord varying degree of importance to different virtues. Previous research have also found that there are differences in values between trainee managers and experienced managers.In this study, managerial virtues are assessed using the Values in Action Inventory of Strengths (VIA-IS).This study which was conducted on Malaysian management undergraduates yielded a different factor structure for the VIA (Virtues in Action) Inventory and provides an indication on the types of moral virtues that are regarded as important in a Malaysian manager from the lens of budding millennial managers.According to Malaysian management business undergraduates, the three most important moral virtues in a manager are collaborative leadership, benevolent philomathy and innovativeness.